2017
DOI: 10.1055/s-0043-112745
|View full text |Cite
|
Sign up to set email alerts
|

Qualitätsindikatoren für Primary-Health-Care-Einrichtungen in Österreich

Abstract: The strengthening of primary health care is one major goal of the current national health reform in Austria. In this context, a new interdisciplinary concept was developed in 2014 that defines structures and requirements for future primary health care facilities. The aim of this project was the development of quality indicators for the evaluation of the scheduled primary health care facilities in Austria, which are in accordance with the new Austrian concept. We used the RAND/NPCRDC method for the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
1
Order By: Relevance
“…First, the method for index pool construction is reasonable. Instead of constructing the index pool based only on the existing index database [ 11 ], this research constructs the index pool based on both the literature research and the analysis of 1651 quantitative data, which makes the measurement system more manoeuvrable and reliable. Second, our indices are comprehensive and reasonable which cover not only the evaluation of service quality for related diseases but also the evaluation of various basic public health service items stipulated by related authorities in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the method for index pool construction is reasonable. Instead of constructing the index pool based only on the existing index database [ 11 ], this research constructs the index pool based on both the literature research and the analysis of 1651 quantitative data, which makes the measurement system more manoeuvrable and reliable. Second, our indices are comprehensive and reasonable which cover not only the evaluation of service quality for related diseases but also the evaluation of various basic public health service items stipulated by related authorities in China.…”
Section: Discussionmentioning
confidence: 99%
“…Countries such as Austria and Poland have optimized the performance of family doctors, the process of collaborative service and other aspects. Standardized assessments are made in the workplace where family doctors provide health services in terms of basic medical services, quality of care, continuity of care, coordination and safety [11][12][13]. A study from Switzerland showed that after optimizing the interior complements of the primary care office, the level of medical and health services and patient satisfaction improved [14].…”
Section: Introductionmentioning
confidence: 99%
“…Gegebenenfalls können Mängel bei der Zusammenarbeit mit anderen Ärzten und Mitarbeitern der Klinik entstehen. In diesem Zusammenhang weisen Semlitsch et al [18] darauf hin, dass die Kooperation unter Ärzten (gemessen u. a. anhand von "Überweisungsqualität" und "Kommunikation innerhalb eines Behandlungsteams") ein wichtiger Qualitätsindikator bei der primären Patientenbehandlung ist. Jedoch tendieren Ärzte, die unter Burnout leiden, zu negativem, zynischem Verhalten [20], was bis zum Verschreiben suboptimaler Therapien führen kann [21].…”
Section: Burnoutunclassified